2011
DOI: 10.1099/ijs.0.022004-0
|View full text |Cite
|
Sign up to set email alerts
|

Chryseobacterium chaponense sp. nov., isolated from farmed Atlantic salmon (Salmo salar)

Abstract: Two bacterial strains, designated Sa 1147-06T and Sa 1143-06, were isolated from Atlantic salmon (Salmo salar) farmed in Lake Chapo, Chile, and were studied using a polyphasic approach. Both isolates were very similar; cells were rod-shaped, formed yellow-pigmented colonies and were Gram-reaction-negative. Based on 16S rRNA gene sequence analysis, strains Sa 1147-06T and Sa 1143-06 shared 100 % sequence similarity and showed 98.9 and 97.5 % sequence similarity to Chryseobacterium jeonii AT1047T and Chryseobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…The only real difference in fatty-acid profiles appeared to be the presence of iso-C 16:0 3-OH, which was not explicitly mentioned for the genus Chryseobacterium (Montero-Calasanz et al, 2014). However, it was reported for a variety of Chryseobacterium species (Hugo et al, 2003; Kämpfer et al, 2003, 2011; Li et al, 2003; Kim et al, 2005; Shen et al, 2005; Young et al, 2005; Park et al, 2006; Behrendt et al, 2007, 2008; Hantsis-Zacharov and Halpern, 2007; Quan et al, 2007; Vaneechoutte et al, 2007; Szoboszlay et al, 2008; Ilardi et al, 2009; Benmalek et al, 2010; Pires et al, 2010; Wu et al, 2013) in concentrations up to 9% and thus does not constitute a real difference either. Additionally, anteiso-C 15:0 as reported for Epilithonimonas is not mentioned in the description of Chryseobacterium but known to occur in the genus from traces to up to 8.2% (Montero-Calasanz et al, 2014).…”
Section: Resultsmentioning
confidence: 96%
“…The only real difference in fatty-acid profiles appeared to be the presence of iso-C 16:0 3-OH, which was not explicitly mentioned for the genus Chryseobacterium (Montero-Calasanz et al, 2014). However, it was reported for a variety of Chryseobacterium species (Hugo et al, 2003; Kämpfer et al, 2003, 2011; Li et al, 2003; Kim et al, 2005; Shen et al, 2005; Young et al, 2005; Park et al, 2006; Behrendt et al, 2007, 2008; Hantsis-Zacharov and Halpern, 2007; Quan et al, 2007; Vaneechoutte et al, 2007; Szoboszlay et al, 2008; Ilardi et al, 2009; Benmalek et al, 2010; Pires et al, 2010; Wu et al, 2013) in concentrations up to 9% and thus does not constitute a real difference either. Additionally, anteiso-C 15:0 as reported for Epilithonimonas is not mentioned in the description of Chryseobacterium but known to occur in the genus from traces to up to 8.2% (Montero-Calasanz et al, 2014).…”
Section: Resultsmentioning
confidence: 96%
“…T115 was highly similar to C. chaponense based upon genetic analysis, which was further supported using the polyphasic ap proach. However, some phys- iological and biochemical differences existed between strain T115 and the C. cha po nense type strain (Kämpfer et al 2011), which possibly suggests strain divergence or that they are distinct species/ subspecies. Although C. cha po nense was originally recovered from diseased fish (Kämpfer et al 2011), results from our experimental challenges demonstrated that strain T115 did not induce major pathological changes when administered IP to several salmonid species and did not result in mortality in any challenged fish.…”
Section: Discussionmentioning
confidence: 99%
“…have recently been described that are associated with diseased farmed fish worldwide, including C. piscicola (Ilardi et al 2009), C. chaponense (Kämpfer et al 2011), C. tructae (Zamora et al 2012b), C. oncorhynchi (Zamora et al 2012a), and C. viscerum (Zamora et al 2012c). During these outbreaks, external lesions (Kämpfer et al 2011), deep ulcerations (Ilardi et al 2010, and signs of septicemia (Zamora et al 2012a,b) were reported in infected fish. Unfortunately, unraveling the pathogenesis of these novel fish-pathogenic chryseobacteria has received little attention.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Chryseobacterium balustinum Chryseobacterium scophtalmum and Chryseobacterium joostei have been isolated from diseased fish [4-6]. More recently, Chryseobacterium piscicola has been reported to produce mortalities in farmed Atlantic salmon ( Salmo salar ) and rainbow trout ( Oncorhynchus mykiss ) in Chile and Finland [7-9], Chryseobacterium arothri was isolated from the kidneys of the pufferfish Arothron hispidus in Hawaii [10] and Chryseobacterium chaponense from diseased farmed Atlantic salmon in Chile [11]. In fact, some Chryseobacterium species are considered potentially emerging pathogens in fish [4].…”
Section: Introductionmentioning
confidence: 99%